2015
DOI: 10.3389/fphys.2015.00312
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Regulation of Toll-like Receptors in Asthma and COPD

Abstract: Asthma and chronic obstructive pulmonary disease (COPD) have both been historically associated with significant morbidity and financial burden. These diseases can be induced by several exogenous factors, such as pathogen-associated molecular patterns (PAMPs) (e.g., allergens and microbes). Endogenous factors, including reactive oxygen species, and damage-associated molecular patterns (DAMPs) recognized by toll-like receptors (TLRs), can also result in airway inflammation. Asthma is characterized by the dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 110 publications
0
75
0
Order By: Relevance
“…Cigarette smoke exposure alters bronchial epithelium resulting in various changes in the release of inflammatory mediators involved in macrophages and neutrophil recruitment and activation [9]. The expression of toll like receptor (TLR) 2 and TLR4 is modified contributing to a potential increased susceptibility for bacterial infections [10,11].…”
Section: @Erspublicationsmentioning
confidence: 99%
“…Cigarette smoke exposure alters bronchial epithelium resulting in various changes in the release of inflammatory mediators involved in macrophages and neutrophil recruitment and activation [9]. The expression of toll like receptor (TLR) 2 and TLR4 is modified contributing to a potential increased susceptibility for bacterial infections [10,11].…”
Section: @Erspublicationsmentioning
confidence: 99%
“…Recently, we have shown that serum levels of the RAGE‐activating DAMPs HMGB1, S100A9 and LL‐37 are increased in COPD patients during exacerbation compared with stable disease . These DAMPs can activate PRRs on neutrophils to induce their recruitment …”
mentioning
confidence: 99%
“…The activation of TLR2/4 induces activation and migration of neutrophils and may thus contribute to the increased airway inflammation during COPD exacerbations . Furthermore, a positive feedback loop has been described in which DAMPs not only activate TLR4, but also induce TLR4 upregulation indicating that the increased expression of TLRs may be a consequence of DAMP release . Thus, increased neutrophilic expression of TLR2 and TLR4 in combination with increased DAMP levels may contribute to DAMP‐induced neutrophilic airway inflammation during COPD exacerbations.…”
mentioning
confidence: 99%
“…In this context, it has been shown that stimuli from the microenvironment can influence IgE-dependent signalling in MCs and can thereby selectively modulate MC responses, for example, through activation of MC interleukin (IL)-33 receptors (IL-33Rs), thymic stromal lymphopoietin receptors (TSLPRs) and toll-like receptors1112. IgE-dependent signalling in MCs also can be modulated by the engagement of (tumour-necrosis factor (TNF)):TNF receptor (TNFR) superfamily molecules.…”
mentioning
confidence: 99%